Food menus within New Zealand primary school canteens: Do they meet the guidance? - Pillay D; Piddington M; Ali A; Wham C (John Wiley and Sons Australia, Ltd on behalf of Australian Health Promotion Association, 2023)
ISSUE ADDRESSED: Unhealthy food and drinks are widely available in New Zealand school canteens. The aim of this study was to assess primary school canteen food menus against the newly implemented Ministry of Health 'Food and Drink Guidance for Schools'. METHODS: A convenience sample of 133 primary school canteen menus was collected in 2020 as part of the baseline evaluation of the Healthy Active Learning initiative across New Zealand. A menu analysis toolkit was developed to assess menus in accordance with the Ministry of Health's 'Food and Drink Guidance for Schools' which classifies food items into three food categories: 'green', 'amber' and 'red'. RESULTS: Most menu items belonged to the less healthy amber (41.0%) and red (40%) food categories. Low decile schools had a lower percentage of green food items (8.6%) and a higher percentage of red food items (48.3%) compared to high decile schools. Sandwiches, filled rolls and wraps were the most commonly available items, followed by baked foods and foods with pastry. Over half of the in-house canteen menu items were classified as 'red' foods (55.3%). CONCLUSIONS: Most school canteens were not meeting the guidelines for healthy food and drink provision outlined by the Ministry of Health. Improving the food environment for children in socio-economically deprived areas needs to be prioritised to reduce inequities. SO WHAT?: This study highlights the unhealthy food environments in New Zealand schools and emphasises the need for more robust national policies and mandated school guidance.
Keywords: childhood nutrition; food policy; healthy active learning; menu audit; policy evaluation; school food environment; traffic-light guidance